PERANCANGAN APLIKASI INVOICE BULANAN APARTEMEN ISTANA HARMONI JAKARTA PUSAT BERBASIS WEB MENGGUNAKAN RAPID APPLICATION DEVELOPMENT (RAD) - Mochamad Adhari Adiguna, M.Kom (PT Triputra Sejahtera Prima, 2023)
In the current millennial era, information technology is developing rapidly. In managing information, technology is needed because information has important value for a company. Likewise in the management process of the Isatanah Harmoni Apartment which prioritizes satisfactory service for its residents. However, until now the existing service system is still manual in terms of monthly invoices. Therefore, a web-based system was designed called the Web-Based Monthly Invoice Design System for Istanah Harmoni Apartments. This system aims to make it easier for residents to view details and confirm payments through the bank quickly and easily. The research method used is qualitative. The development model used is the SDLC method and uses the Unified Modeling Language (UML) modeling using the PHP and MySQL programming languages. While the software tools used are Notepad++ and MySQL as the database. This design system is expected to provide much better changes and provide effective invoice reports as well as structured data documentation.